KONSUMSI AIR MINUM SERTA KONSUMSI DAN KECERNAAN BAHAN KERING PAKAN KELINCI LOKAL YANG MENDAPATKAN HIJAUAN BERBEDA - Pembeu, Merlin; Nirwana, Nirwana (AgriSains, 2016)
One strategis to provide feed in developing rabbits in the dry areas is utilising forage that are able to survive in during dry season. This experiment was aimed to examine the use of different forages on water intake, feed intake and digestibility of local rabbit. The experiment employedÂ  20 male local rabbits, consentrate feed 2% of live weight and forage ad libitum, metabolisme cages and also supporting equipments. The experiment design used was randomised block design, which consisted of 4 treatments and 5 replicates. The dietary treatments were P1 (MO) = Moringa oleifera, P2 (LL)= Leucaena leucocephala, P3 (DV)= Desmanthus virgatus, and P4 (TI)= Tamarindus indica.The result showed thatÂ  different forage affected very significantly (P<0.01) feed intake. However, treatment did not affect significantly (P>0,05) water intake and feed digestibility of local rabbit. It was concluded the best forage for local rabbit is Desmanthus virgatus.Key words: Drink water, Digestibility, Consumption, Forage, Local rabbit